Dynamic light application therapy to reduce the incidence and duration of delirium in intensive-care patients: a randomised controlled trial. Issue 3 (March 2016) - Simons, Koen S; Laheij, Robert J F; van den Boogaard, Mark; Moviat, Miriam A M; Paling, Anne J; Polderman, Florens N; Rozendaal, Frans W; Salet, Geertruda A M; van der Hoeven, Johannes G; Pickkers, Peter; de Jager, Cornelis P C
Summary: Background: Disturbed circadian rhythm is a potentially modifiable cause of delirium among patients in intensive-care units (ICUs). Bright-light therapy in the daytime can realign circadian rhythm and reduce the incidence of delirium. We investigated whether a high-intensity dynamic light application (DLA) would reduce ICU-acquired delirium. Methods: This was a randomised, controlled, single-centre trial of medical and surgical patients admitted to the ICU of a teaching hospital in the Netherlands. Patients older than 18 years, expected to stay in the ICU longer than 24 h and who could be assessed for delirium were randomised to DLA or normal lighting (control), according to a computer-generated schedule. The DLA was administered through ceiling-mounted fluorescent tubes that delivered bluish-white light up to 1700 lux between 0900 h and 1600 h, except for 1130–1330 h, when the light was dimmed to 300 lux. The light could only be turned off centrally by investigators. Control light levels were 300 lux and lights could be turned on and off from inside the room. The primary endpoint was the cumulative incidence of ICU-acquired delirium. Analyses were by intention to treat and per protocol. The study was terminated prematurely after an interim analysis for futility. This study is registered withClinicaltrials.gov, numberNCT01274819 . Findings: Between July 1, 2011, and Sept 9, 2013, 734 patients were enrolled, 361 in the DLA group and 373 in the control group. Delirium occurred in 137 (38%) of 361 DLA patients and 123 (33%) of 373 control patients (odds ratio 1·24, 95% CI 0·92–1·68, p=0·16). No adverse events were noted in patients or staff. Interpretation: DLA as a single intervention does not reduce the cumulative incidence of delirium. Bright-light therapy should be assessed as part of a multicomponent strategy. Funding: None.